A Smart product co-design and monitoring framework via gamification and complex event processing - Loizou, Spyros; Elgammal, Amal; Kumara, Indika; Christodoulou, Panayiotis; Papazoglou, Mike; Andreou, Andreas S. (My University, 2019)
In the traditional software development cycle, requirements gathering is considered the most critical phase. Getting the requirements right early has become a dogma in software engineering because the correction of erroneous or incomplete requirements in later software development phases becomes overly expensive. For product-service systems (PSS), this dogma and standard requirements engineering (RE) approaches are not appropriate because classical RE is considered concluded once a product service is delivered. This paper proposes a novel framework that enables the customer and the product engineer to co-design smart products by integrating three novel and advanced technologies to support: view-based modelling, visualization and monitoring, i.e., Product-Oriented Configuration Language (PoCL), gamification and Complex Event Processing (CEP), respectively. These create a “digital-twin” model of the connected ‘smart’ factory of the future. The framework is formally founded on the novel concept of manufacturing blueprints, which are formalized knowledge-intensive structures that provide the basis for actionable PSS and production “intelligence” and a move toward more fact-based manufacturing decisions. Implementation and validation of the proposed framework through real-life case studies are ongoing to validate the applicability, utility and efficacy of the proposed solutions.
Keywords: Product-service Systems; Smart Product; Customization; Product-oriented Configuration Language; PoCL; Gamification; PSS Monitoring; Complex Event Processing